Faktor-Faktor Yang Memengaruhi Perubahan Laba Pada Perusahaan Perbankan - Christian Crespo; Hermaya Ompusunggu (Politeknik Ganesha Medan, 2023)
Profit changes is the fluctuation of the profit company earned at a certain period. Companies naturally want their profit to grow every period, so as banking companies. This matter happen because of various factors. This research uses non-performing loan, loan to deposit ratio and dividend payout ratio as variables, with the purposes of seeing the impact of non-performing loan, loan to deposit ratio and dividend payout ratio partially and simultaneously on profit changes of banking companies. This research has 47 banking companies that are recorded on the Indonesia Stock Exhange as its population, and with the use of purposive sampling technique, the amount of sample of this reseach is 11 banking companies. This research uses quantitative method with secondary data which is financial report that is collected by using documentation method. Data analysis methods used in this research are descriptive analysis, classical assumption test, multiple linear regression analysis. Through the T test, the results are non-performing loan has no significant impact on profit changes, loan to deposit ratio has no significant impact on profit changes and dividend payout ratio has significant impact on profit changes. Through the F test, it was found that non-performing loan, loan to deposit ratio and dividend payout ratio simultaneously has no significant impact on profit changes. From the result of the coefficient of determination, it is said that these three variable only describe 4,5% of profit change, with other 95,5% being describe by other variable.